Pengembangan Aplikasi Media Pembelajaran Pengenalan Binatang untuk Usia Dini dengan Realitas Tertambah Berbasis Android - Abdul Habib Hadil; Harya Bima Dirgantara (UNIVERSITAS KALBIS, 2022)
The purpose of this research is to develop Learning Media for Animal Recognition by utilizing Augmented Reality technology that runs on smartphones. Augmented reality is a technology in smartphones that can visualize virtual objects such as 2D and 3D models in the real world. This research uses the Multimedia Development Life Cycle method to develop applications. Application development is equipped with an explanation information feature. This research uses Unity software as a tool for application development and Vuforia Software Development qwerty regarding the use of augmented reality technology. The results of the application development in the form of a file with the extension. Apk in order to see real animals and test results, 80% (4 people) of respondents stated that this application is easy to use to recognize animal names for an early age with augmented reality.